2017
DOI: 10.1177/1538574417697211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Anemia and Postoperative Hemoglobin Drop on the Incidence of Acute Kidney Injury and In-Hospital Mortality in Patients With Type B Acute Aortic Syndromes Undergoing Thoracic Endovascular Aortic Repair

Abstract: Preoperative Hb and postoperative Hb drop were significant risk factors for AKI. Postoperative Hb drop and Hb levels predicted in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
1
22
0
1
Order By: Relevance
“…In patients undergoing thoracic endovascular aortic repair, Gorla et al identified preoperative hemoglobin levels and postoperative hemoglobin levels decrease as risk factors for AKI and in-hospital mortality [60].…”
Section: Complete Blood Count Parameters and Akimentioning
confidence: 99%
“…In patients undergoing thoracic endovascular aortic repair, Gorla et al identified preoperative hemoglobin levels and postoperative hemoglobin levels decrease as risk factors for AKI and in-hospital mortality [60].…”
Section: Complete Blood Count Parameters and Akimentioning
confidence: 99%
“…Yet information about the relationship between Hb and ABAD is limited. Gorla et al suggested that Hb was independently related to in-hospital outcomes of acute aortic syndrome (AAS) post-TEVAR (18), though 2year outcomes were not independently associated with Hb levels. However, given its relatively small sample, further studies on the relationship between Hb and ABAD outcomes remain meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, even though some studies demonstrate an independent association between perioperative blood transfusion and adverse postoperative outcomes, [24][25][26][27] it is worthwhile to note that patients who are transfused perioperatively, in general, tend to be sicker and have several comorbid conditions including anemia which independently increase their risks of postoperative adverse outcomes. [28][29][30][31] Nonetheless, that PRBCs contain proinflammatory cytokines which increase systemic inflammatory response, and have been noted to adhere to vascular endothelium leading to reduced microvascular flow and tissue hypoxia 25,32,33 demonstrate that emphasis should be placed on continuous cardiac monitoring of patients who undergo perioperative blood transfusions. The effect of mechanical ventilation on cardiovascular performance is well-reported.…”
Section: Discussionmentioning
confidence: 99%